THE QUANTITATIVE AND QUALITATIVE PARAMETERS OF THE BODOC SPRINGS - VIGH, Melinda (Studia Universitatis Babeș-Bolyai Ambientum, 2021)
The post-volcanic phenomena in the Bodoc area are part of the alignment that flanks the western strip of the Carpathian Chain. The fragmented geological structure facilitated the migration of water and gas to the surface. The characteristics of spring water have been studied since the 19th century. On the outskirts of the Bodoc village there are several springs, the most important are Matild, Lenes and Geza. The analysis of water samples was performed in the field (the main parameters) and in the laboratory (major ions). The main water parameters determined in situ where: pH, redox potential, temperature, electrical conductivity, total dissolved solids and salinity, and in the laboratory, where determined the following ions: sodium, calcium, magnesium, ammonia, potassium, lithium, fluorides, chlorides, bromides, nitrites, nitrates, phosphates, sulphates, bicarbonates. The analysis of the parameters shows many similarities, because the springs have the same source or neighbouring sources. At the same time, differences were identified in the case of some parameters, which occurred due to the influence of local factors.